Association Between Juxtapapillary Duodenal Diverticula and Risk of Choledocholithiasis: a Systematic Review and Meta-analysis - Karn Wijarnpreecha (2019)
© 2018, The Society for Surgery of the Alimentary Tract. Background/Objectives: Studies have suggested that the presence of juxtapapillary duodenal diverticula (JDD) could be a predisposing factor for choledocholithiasis. This systematic review and meta-analysis was conducted with the aims to summarize all available evidence to better characterize the risk. Methods: A literature search was performed using MEDLINE and EMBASE database from inception to January 2018. Cross-sectional studies that reported odd ratios (OR) comparing the risk of choledocholithiasis among individuals with JDD versus individuals without JDD were included. Pooled OR and 95% confidence interval (CI) were calculated using a random-effect, generic inverse variance method. Results: Of 527 retrieved articles, 11 studies met our eligibility criteria and were included in analysis. We found a significant association between the presence of JDD and choledocholithiasis with the pooled OR of 2.30 (95% CI, 1.84–2.86). The statistical heterogeneity was moderate with an I 2 of 60%. Conclusions: A significantly increased risk of choledocholithiasis among individuals with JDD was observed in this study.